Population aging, silver dividend, and economic growth - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2023)
While there are growing concerns about population aging, some studies explore the possibility that population aging can give rise to a silver dividend that contributes to economic growth (ADB 2019). While the demographic dividend refers to the increase of the working-age population, the silver dividend points to increased longevity and longer working life as potential sources of growth in an aging society. Extending Lee and Shin (2021) to include developing countries, we examine the potential for a silver dividend by investigating the channels through which population aging affects economic growth. We find that lower total factor productivity growth is the main mechanism through which population aging harms economic growth. Labor shortage caused by population aging is mostly offset by higher labor force participation rates of males, females, and older workers. In particular, the labor force participation rate of the older people increases the most.
Keywords: J10; O40; J21; O47; E2; 330; aging; growth; labor force participation; total factor productivity; silver dividend